The Influence of Work Environment and Organizational Culture on Work Productivity at PT Siraj Badawi Cukup Rupiah (Surabraja) - Tasya Vanisa; Luciano Garai Alasti Yacobi; Syahrul Mubarak; Siti Maryam (Universitas KH. Abdul Chalim Mojokerto, 2025)
Human resources play a crucial role in every activity of a company, which must be supported by a conducive work environment and a structured organizational culture. The objective of this analysis is to conduct a study on how the roles of the work environment and organizational culture affect work productivity at PT Siraj Badawi Cukup Rupiah. The population of this research consists of all employees of Siraj Badawi Cukup Rupiah (SURABRAJA), totaling 160 individuals, and this study employs a census method (total sampling). The researcher utilizes multiple linear regression analysis, as this study involves more than one independent variable to explain the variance in the dependent variable, using SPSS as a tool. The findings of this research confirm that (1) the work environment has a positive and significant effect on work productivity partially, (2) organizational culture has a positive and significant effect on work productivity partially, and (3) both the work environment and organizational culture have a positive and significant effect on work productivity simultaneously. A positive and strong organizational culture can enhance productivity by creating an environment that fosters collaboration, innovation, accountability, and commitment.